THE ATTITUDE OF ROHINGYA TEENAGERS TOWARDS THEIR LANGUAGE - Lonni Nur Iffah Nasution Lonni Nur Iffah Nasution (Journal of English Education and Linguistics, 2020)
This study deals with language attitude of Rohingya teenagers toward their ethnic language in Medan. A qualitative descriptive research design was applied. The aim of the study is to know the attitudes of Rohingya teenagers towards their ethnic language. The subject of this research are eighteen of the Rohingya teenagers at the age 15-21 years old. The instruments used for this study were observation and interview. The data was analyzed by using interactive models of Miles & Huberman (1984) technique. Based on the data analysis, it was found that Rohingya teenagers realized their language attitude in three ways, i.e: they use Rohingya language at home, they use Rohingya language at religion domain and they use Rohingya language in friendship domain. It was also found that the attitudes of the Rohingya teenagers caused by some reason, i.e: because they are loyal and maintain the Rohingya language, because they are proud and make the Rohingya language as their identity, and because they have awareness of language norms towards Rohingya language.